Prediction of steel tower foundation specifications using non-destructive testing method - Ryu, Hee Hwan; Choi, Suyoung; Hong, Eun Soo; Choi, Shin Kyu (Geomechanics and Engineering, 2025)
Transmission tower foundations play a critical role in supporting and preventing the collapse of tower structures. In Korea, 12,000 tower foundations require additional reinforcement due to the recent design standard changes for wind speed pressure as a result of climate change. However, several challenges arise when attempting to determine appropriate methods of reinforcement, especially in the case of approximately 1,500 towers that lack any records of foundation specifications. In this study, the electrical resistivity survey, one of the non-destructive testing methods, is employed to accurately determine foundation specifications, which can in turn be used to strategically develop reinforcement plans. Using electrical resistivity survey data obtained through both laboratory and field experiments, an algorithm capable of extracting foundation specifications was developed. The system was then applied to 47 transmission tower foundations. According to the results, the electrical resistivity survey achieved a prediction accuracy of 91.5% for depth of the tower foundation, 98.6% for width of the base slab, and 95.6% for thickness of the base slab. These findings suggest that the method is particularly effective at predicting the width and thickness of the base slab, with width predictions being the most accurate. This research is expected to aid in the creation of maintenance and reinforcement plans for transmission tower foundations while also enabling cost-effective specification assessments for various buried civil engineering structures.
Keywords: Base slab; Design standard; Electrical resistivity survey; Nondestructive testing method; Nondestructive tests; Resistivity surveys; Steel towers; Tower foundations; Tower structures; Transmission tower; electrical resistivity survey; foundation; non-destructive test; specification; transmission tower